Lexical and Stylistic Features of Translating Old Russian Literary Monuments into Russian and English Languages (“The Tale of Igor’s Campaign”) - V. N. Onoshko (Научный диалог, 2024)
This article explores the peculiarities of translating military vocabulary from the Old Russian literary monument “The Tale of Igor’s Campaign” into Russian and English languages through the analysis of translations by D.S. Likhachov, O.V. Tvorogov (modern Russian language), V. Nabokov, and I. Petrova (English language). The study employed methods such as the method of complete sampling, contextual analysis method, comparative method, and quantitative analysis method. The research focused on 34 lexical units used in 128 contexts. Based on the conducted study, the following conclusions can be drawn. (1) Translators of the aforementioned work into Russian mostly replaced archaic words with contemporary ones etymologically related to the original word, while preserving archaic words to convey historical color in translations. (2) Translations of the work into English showed translators’ tendency towards fidelity to the original text through the use of full and partial equivalents, approximate translation, and the method of generalization (selecting a word with broader meaning). Thus, the analysis of lexical units and their translation methods into modern Russian and English languages revealed translators' inclination to choose the translation variant closest to the original unit.